Informal mentoring among foster youth entering higher education. (January 2021) - Gowdy, Grace; Hogan, Sean
Highlights: We study what types of informal mentorship are available to young people connected to the foster care system. We explore how social capital can help our understanding of this effort. We examine what types of support are available in each type of mentoring relationship. Abstract: Informal mentoring, anaturally-occurringcaring relationship with a non-parental adult, has been shown to promote positive outcomes for young people, including youth transitioning out of the foster care system. Although we often talk about mentoring as one homogenous experience, recent research has demonstrated there are important variations in who mentors are and what supports they offer. Using survey data provided on youths' social networks, this study identified 378 informal mentoring relationships provided to 113 former and current foster youth preparing to enter a four-year university. Cluster analysis identified two primary types of mentoring relationships in accordance with previous literature: core and capital mentoring. Following the cluster analysis, type of mentoring relationship was examined across various types of support (instrumental, informational, and emotional support). Findings indicated core mentoring relationships were more predominantly associated with instrumental support, while capital mentoring related more closely with informational support. There were no significant differences between mentoring type and emotional support or youth-rated closeness to mentor. The implications for facilitating socio-emotional support for foster youth are discussed.